2022
DOI: 10.3390/genes13040706
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Type 1 Diabetes: Established Facts and New Insights

Abstract: Type 1 diabetes (T1D) is an autoimmune disease characterized by the T-cell-mediated destruction of insulin-producing β-cells in pancreatic islets. It generally occurs in genetically susceptible individuals, and genetics plays a major role in the development of islet autoimmunity. Furthermore, these processes are heterogeneous among individuals; hence, different endotypes have been proposed. In this review, we highlight the interplay between genetic predisposition and other non-genetic factors, such as viral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 156 publications
(307 reference statements)
0
20
0
Order By: Relevance
“…From these, 1182 isolates could be assigned to 16 different GPSCs and represent 123 STs and 20 serotypes (Table 1). The vast majority (92.4%) of isolates belong to GPSCs6 (424), GPSC8 (363), GPSC38 (110), GPSC53 (100), and GPSC43 (95). Notably, only one member (BioSample: SAMEA3233202) of GPSC9 -a dominant cluster -harbored a gadB Spn gene.…”
Section: Resultsmentioning
confidence: 99%
“…From these, 1182 isolates could be assigned to 16 different GPSCs and represent 123 STs and 20 serotypes (Table 1). The vast majority (92.4%) of isolates belong to GPSCs6 (424), GPSC8 (363), GPSC38 (110), GPSC53 (100), and GPSC43 (95). Notably, only one member (BioSample: SAMEA3233202) of GPSC9 -a dominant cluster -harbored a gadB Spn gene.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it may be suggested that inflammatory reactions around pancreatic islets have occurred in PBS and BLPs group at this time (21-week-old), and therefore a decline of the glucose sensitivity of β cells was induced (Siewko et al., 2014 ). The interplay of various pathogenic factors contributes to the initiation of these inflammatory reactions on pancreatic β cells during T1DM development, and β-cell dysfunction may exist years before T1DM diagnosis (Zajec et al., 2022 ; Evans-Molina et al., 2018 ). Therefore, theoretically, interventions such as immunomodulatory therapies should be applied as early as possible to maintain β-cell function and prolong β-cell insulin production (Mastrandrea & Quattrin, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In T1DM, insulin-producing pancreatic β cells are recognized and destroyed by the self-reactive immune responses, resulting in insulin deficiency, and therefore, T1DM patients require lifelong therapy with exogenous insulin (Katsarou et al., 2017 ). The etiology of T1DM is complicated and multifactorial, including genetic, immunological, epigenetic, environmental, physical, and social factors, resulting in the breakdown of autoimmune tolerance (Zajec et al., 2022 ; Chwalba et al., 2021 ; Bluestone et al., 2010 ; Bauer et al., 2021 ). However, the detailed underlying mechanisms have not been fully elucidated and remain to be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Through interactions with immune cells, pancreatic cells also seem crucial in starting pathogenic processes. β-Cells appear to be more active participants in the disease's development than previously thought and are not merely passive targets (Li et al, 2021, Zajec et al, 2022. The present work aimed to investigate serum levels of thyroid autoantibodies and their correlation with thyroid function and tumor necrosis factor-alpha (TNF-α) in T1DM patients compared to randomly selected healthy individuals.…”
Section: Introductionmentioning
confidence: 96%